Comprehension of Mandarin Aspect Markers by Preschool Children With and Without Developmental Language Disorder - Chen, Lijun; Durrleman, Stephanie (Frontiers in Psychology, 2022)
Children with developmental language disorder (DLD) reportedly struggle with the comprehension of aspect. However, since aspect and tense are closely entangled in the languages spoken by the children with DLD in previous studies, it is unclear whether the difficulty stems from aspect, tense, or both. Mandarin Chinese, a language without morphological manifestations of tense, is ideal to investigate whether the comprehension of aspect is specifically affected in children with DLD, yet to date work on this is scarce and presents methodological limitations. In this study, we examined whether preschool Mandarin-speaking children with DLD have difficulty in comprehending perfective aspect (represented with the aspect marker -le) compared to imperfective aspect (represented with the aspect markers zai- and -zhe), whether performance can be explained in terms of the pre- vs post-verbal realization of the aspect markers, and the potential role played by lexical aspect in the comprehension of grammatical aspect. Fourteen preschool children with DLD (mean: 61.11 months old) and 14 TD children (age: 63.4 months old) matched for age and nonverbal intelligence participated in a sentence-picture matching task. Global results showed that, similar to their TD peers, children with DLD performed better on imperfective aspect than perfective aspect. Concerning specific aspect markers, while children with DLD indeed performed similarly to TD children on imperfective -zhe, they obtained significantly lower accuracy than TD children on perfective -le and imperfective zai-. However, considering verb types combined with these aspect markers, results revealed that children with DLD scored significantly higher on the prototypical combination(s) (e.g., zai-+Activity verbs) than on the non-prototypical combination(s) (e.g., zai-+Accomplishment verbs). The performance pattern suggests that the comprehension of aspect markers by children with DLD is particularly affected by lexical aspect. As this also affects younger TD children, children with DLD are arguably at an earlier stage of aspectual development than their age and nonverbal intelligence matched TD peers. Therefore, the aspectual development of children with DLD appears to be delayed rather than deviant. Given this, language programs addressing difficulties in DLD may need to incorporate training on the use of aspect markers, especially targeting their combination with non-prototypical verbs.